Psychiatric Illness in the Paediatric Population Presenting to a Psychiatry Clinic in a Tertiary Care Centre - Risal, A; Sharma, P P (Kathmandu University Medical Journal, 2012)
Background A variety of psychiatric manifestations can be seen in children below the age of 18 years. Such cases rarely present directly to psychiatric care. Methods Retrospective study in Tertiary care hospital . The study population included all the patients of paediatric age group presenting to Psychiatry Outpatient Department of Dhulikhel Hospital directly or referred by a paediatrician or other specialists from October 2008 to October 2010. Results Among the paediatric population evaluated in the psychiatry clinic for two years from October 2008 to October 2010 (N=168), 66.7% were in the age group 15-18 years mean = 14.77 (±2.99), 71.4% were female and 42.3% belonged to Brahmin cast. The highest number of (15%) patients was seen during the month of August 2010. Six months analysis of the psychiatric illnesses of the patients from April 2010 up to October 2010 (n=80) showed dissociative disorder (15%), and seizure disorder (15%) to be the most common diagnoses, followed by depressive disorder and intentional self harm (ISH) (13.8% each). 15% of patients were found to be treated by magico-religious means, with the majority of patients (66.7%) diagnosed as having dissociative disorder. Conclusion The majority of the paediatric population presenting to a psychiatry clinic were in the age group 15-18 years and of female sex. Dissociative disorder was the most common diagnosis followed by depressive disorders. The majority of patients with dissociative disorder had previously been treated by magico-religious means. http://dx.doi.org/10.3126/kumj.v8i4.6235 Kathmandu Univ Med J 2010;8(4):375-81